Imaging of nerve injury in neonatal acute bilirubin encephalopathy using 1H-MRS and Glu-CEST techniques - Lin, Qihuan; Chen, Lanmei; Zheng, Hongyi; Tan, Hui; Zhang, Gengbiao; Zheng, Wenbin (Frontiers in Neuroscience, 2023)
Objectives To investigate the significance of proton magnetic resonance spectroscopy (1H-MRS) and glutamate chemical exchange saturation transfer (Glu-CEST) techniques in assessing the condition and prognosis of acute bilirubin encephalopathy patients and to understand the mechanism of nerve injury in this disease. Materials and methods From September 2019 to February 2021, 31 neonates with acute bilirubin encephalopathy and 16 healthy neonates were enrolled in this study. All the quantitative results of 1H-MRS, Glu-CEST, and conventional magnetic resonance imaging (MRI) of all neonates were analyzed. The associations between statistically significant indicators of imaging and developmental quotients (DQ) were analyzed. Results The 31 cases were assigned to the mild subgroup (n = 21) and moderate and severe subgroup (n = 10) according to the bilirubin-induced neurologic dysfunction (BIND) scores. The case group had elevated Cho and GABA absolute concentrations compared to the normal control group (all p < 0.05). Compared with the normal control group, the absolute concentration of GABA of the moderate and severe subgroup was significantly larger (p < 0.05). Compared with the normal control group, the Glu-CEST% values in the left basal ganglia, right thalamus, left frontal cortex and bilateral medial geniculate body of the case group was significantly larger (all p < 0.05). The moderate and severe subgroup had higher Glu-CEST% values in the left basal ganglia, right thalamus, and bilateral medial geniculate body than the normal control group (all p < 0.05). A negative association was revealed between the DQ scores and the Glu-CEST% values in the left basal ganglia (r = −0.888, p < 0.05). Conclusion The combination of 1H-MRS and Glu-CEST techniques can monitor the intracerebral metabolite level of acute bilirubin encephalopathy and evaluate the illness severity.